Pendampingan Pengembangan Komponen Instrument Terpadu (KIT) Fisika Terbang untuk SMK Penerbangan - Mufti Arifin; Endah Yuniarti; Syarifah Fairuza (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
The lack of adequate physics laboratory facilities for conducting flight physics practicums in Aviation Vocational High Schools has been a significant obstacle in the learning process. Due to these limitations, students' understanding of the physics concepts underlying aviation principles has been suboptimal. To address this issue, community service activities have focused on enhancing the capacity of teachers at Gutama Aviation Vocational High School to design and implement physics practicums. Through the creation and utilization of Integrated Instrument Kits (KIT) for flight physics, it is hoped that teachers can provide more concrete and engaging learning experiences for students. With the successful development of 5 KITs, teachers now have the skills to design a variety of practical activities that meet the needs of their students. Additionally, the provided mentorship has equipped teachers with a deep understanding of physics concepts relevant to the aviation industry. It is hoped that the success of this activity can improve the quality of physics education at Gutama Aviation Vocational High School, encourage teachers to be more innovative in developing additional KITs, and prepare graduates who are more competent in the field of aviation.